2020
DOI: 10.1177/1357633x20943337
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for a telemedicine-delivered healthy lifestyle programme

Abstract: Introduction Effective weight-management interventions require frequent interactions with specialised multidisciplinary teams of medical, nutritional and behavioural experts to enact behavioural change. However, barriers that exist in rural areas, such as transportation and a lack of specialised services, can prevent patients from receiving quality care. Methods We recruited patients from the Dartmouth-Hitchcock Weight & Wellness Center into a single-arm, non-randomised study of a remotely delivered 16-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A recent study showed that people who had to travel for 31-45 min were more likely to trade inperson visits for telehealth options. 20 Additionally, telemedicine can provide access to healthcare without disrupting one's workday or reducing daily wages. 19 These advantages have been summarized in Figure 3.…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that people who had to travel for 31-45 min were more likely to trade inperson visits for telehealth options. 20 Additionally, telemedicine can provide access to healthcare without disrupting one's workday or reducing daily wages. 19 These advantages have been summarized in Figure 3.…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%
“…Individuals can save time that would otherwise be spent traveling and waiting for appointments. A recent study showed that people who had to travel for 31–45 min were more likely to trade in‐person visits for telehealth options 20 . Additionally, telemedicine can provide access to healthcare without disrupting one's workday or reducing daily wages 19 .…”
Section: Telemedicine: a Possible Solution For Obesitymentioning
confidence: 99%